High prevalence of epilepsy in onchocerciasis endemic regions in the Democratic Republic of the Congo - Levick, B.; Laudisoit, A.; Tepage, F.; Ensoy-Musoro, C.; Mandro, M.; Bonareri Osoro, C.; Surkerbuyk, P.; Kashama, J.M.; Komba, M.; Tagoto, A.; Falay, D.; Begon, M.; et al. (Public Library of Science, 2017)
An increased prevalence of epilepsy has been reported in many onchocerciasis endemic areas. The objective of this study was to determine the prevalence of epilepsy in onchocerciasis endemic areas in the Democratic Republic of the Congo (DRC) and investigate whether a higher annual intake of Ivermectin was associated with a lower prevalence of epilepsy.